2020
DOI: 10.1093/rheumatology/keaa842
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of the COVID-19 pandemic on Dutch people with and without an inflammatory rheumatic disease

Abstract: Objectives To determine the psychological impact of the COVID-19 pandemic on people with and without an inflammatory rheumatic disease and establish whether psychological flexibility buffers this impact. Methods From online surveys in the general Dutch population in 2018 and during the peak of the COVID-19 pandemic in 2020, we analysed data of people with (index group, n = 239) and without (control group, n = 1821) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
5
20
0
Order By: Relevance
“…Similar results were reported by Glintborg et al [ 20 ] in more than 12 000 Danish patients with inflammatory rheumatic diseases, in whom high levels of anxiety and self-isolation persisted even after the Danish epidemic was well controlled; poor QoL, which was evaluated with the European QoL five dimensions (EQ-5D), was among the factors associated with both anxiety and self-isolation. Koppert TY et al [ 28 ] examined the psychological impact of the peak of the COVID-19 crisis on 239 Dutch patients with an inflammatory rheumatic disease and 1821 controls. Patients from the former group were more worried and stressed during the peak of the COVID-19 pandemic, although their level of mental wellbeing was not reduced (compared to 2018); authors assessed mental wellbeing with the Dutch version of the RAND 36-item Short Form health survey and described a similar percentage to ours of their patients self-referred being worried/very worried with the peak period of COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Glintborg et al [ 20 ] in more than 12 000 Danish patients with inflammatory rheumatic diseases, in whom high levels of anxiety and self-isolation persisted even after the Danish epidemic was well controlled; poor QoL, which was evaluated with the European QoL five dimensions (EQ-5D), was among the factors associated with both anxiety and self-isolation. Koppert TY et al [ 28 ] examined the psychological impact of the peak of the COVID-19 crisis on 239 Dutch patients with an inflammatory rheumatic disease and 1821 controls. Patients from the former group were more worried and stressed during the peak of the COVID-19 pandemic, although their level of mental wellbeing was not reduced (compared to 2018); authors assessed mental wellbeing with the Dutch version of the RAND 36-item Short Form health survey and described a similar percentage to ours of their patients self-referred being worried/very worried with the peak period of COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Partial or complete closure of outpatient clinics has been implemented in many countries, which has negatively impacted the management and disease course of rheumatic diseases [ 16 19 ]. In addition, negative emotions, psychological conditions, and changes in patient’s behavior, such as non-adherence to medication, had already been described in a substantial number of rheumatic patients [ 20 28 ] and recognized as risk factors for the poor QoL [ 20 , 27 ]. However, in previous studies, QoL assessment has been reduced to physical and psychological health, limiting the comprehensiveness of the topic.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a group of Italian non-infected women aged between 28 and 50, SF-36 scores were significantly decreased (10). However, a Dutch study did not find the level of mental well-being during the peak of COVID-19 to be lower than in 2018 (24). This discrepancy could be due to the differences in participant selection criteria, the times the studies took place regarding the pandemic course, and the variations in COVID-19-related restrictions from country to country throughout the pandemic.…”
Section: Physical and Psychosocial Well-being Of The General Public Amid The Covid-19 Pandemicmentioning
confidence: 90%
“…International evidence published so far shows that the COVID-19 pandemic has negatively impacted on global mental health [5][6][7][8], confirming concerns expressed very early in the outbreak about subsequent mental health consequences arising from this imminent global health crisis [9]. Although a significant amount of research examining the psychological impact of the pandemic has focused on healthcare workers [10][11][12] and clinical populations [13][14][15][16][17][18], there is some evidence suggesting that the psychological distress related to depression, anxiety and posttraumatic stress has impacted the general population as well. A recent meta-analytic review of 23 studies in the general population found that nearly half of participants surveyed in those studies experienced significant psychological impact during the pandemic, with reported prevalence rates reaching 15%, 24% and 26% for posttraumatic stress symptoms (PTSS), depression and anxiety levels, respectively [6].…”
Section: Introductionmentioning
confidence: 86%